Psychometric validation of the Brazilian version of the interpersonal behavior questionnaire in physical education - Bordoni Caldeira, Hermê Fellipo; Correia Júnior, Jânio Luiz; Albuquerque da Costa, Julio Cezar; dos Santos Ferreira, Giovana; Pereira da Silva, Samara Cecília Sabino; Pereira Gonçalves, Marina; Burgueño, Rafael; Freitas-Dias, Ricardo (Springer Nature, 2026)
Grounded on Self-Determination Theory, this study aimed to validate the internal structure and internal consistency of the Brazilian version of the Interpersonal Behavior Questionnaire in Physical Education (IBQ-PE-BRA) among Brazilian adolescents. A total of 500 students (51.2% female), aged 11–17 years (M = 13.82, SD = 1.77), completed the IBQ-PE-BRA. Confirmatory Factor Analysis supported the model’s adequacy, and additional Item Response Theory analyses identified items with insufficient discrimination, indicating a low ability to differentiate between different levels of the construct. The internal consistency measure was satisfactory for the Autonomy-Supportive Behaviors, Competence-Supportive Behaviors, and Relatedness-Supportive Behaviors factors. On the other hand, the three types of need-thwarting behavior obtained unsatisfactory scores. The results of the present study provide important insights for researchers and professionals who intend to use the IBQ-PE-BRA as a tool for assessing students’ perceptions of Physical Education teachers’ behaviors.
Keywords: Ejercicio físico - Estudio y enseñanza; Need-supportive styles; Need-thwarting styles; Controlling behavior; Internal structure validity; Reliability